VALUE-ADDED SERVICES IN SITUATED TRANSLATION TRAINING CONTEXTS: FROM PROJECTS TO PORTFOLIOS - Calvo, Elisa (2017)
This paper analyzes the potential benefits of including value-added services content as a means of diversifying translation training curricula. ‘Value-added service’ is a term used in the language industry (EN 15038, 2006; ISO 17100, 2015) to refer to an open catalogue of differentiated language services offered by Language Service Providers (LSP). Such services require the exercise of basic core translation and intercultural skills but also entail differences when compared to more general, conventional translation tasks. Differentiation factors include specific technological input and different processes, formats and managerial frameworks, each of which require specific skills from the language professional. From a situational perspective (Calvo, 2015; González-Davies y Enríquez-Raído, 2016; Risku, 2002, 2009, 2016; Vienne, 1994), this paper reviews different approaches to the use of projects and portfolios in translator training contexts. An innovative, integrative work model is also presented, as a framework for bringing students into contact with different facets of the language industry today: e.g., marketing translation, editing, project management, post-editing, intercultural consulting, and transcreation. The paper thus shows how a vocational, highly-specialized project (retrospective approach) can be developed into a more transferable, more significant learning experience (prospective approach) (Calvo, 2015).